IMPLICATIONS SOCIO-JURIDICAL CRIMINAL CHARGES RELATED TO ALLEGED MALPRACTICE MEDICAL DOCTOR - Muh Endriyo Susila; Dirwan Suryo Soularto (UNTAG Law Review, 2017)
The lack of legislation governing medical malpractice issue has placed doctors in Indonesia in vulnerable position. They may easily be exposed to the criminal litigation when medical treatment goes wrong. Negligence which results in injury or death amounts to criminal prosecution according to the existing law as it can be seen in Dr. Ayu's case. The infliction of criminal punishment upon three obstetricians in the late 2013 (in Dr. Ayu's case) was both controversial and phenomenal. It has stimulated the national action of strike among doctors and skepticism about law and its enforcement in Indonesia. Trembling with fear of criminal prosecution may encourage doctors in Indonesia to practice defensive medicine. This paper will make analyses on the implication of the criminal prosecution of doctors from socio-juridical perspective.